2019
DOI: 10.1111/apt.15490
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of non‐hypervascular hypointense nodules on Gd‐EOB‐DTPA‐enhanced MRI in patients with chronic hepatitis C

Abstract: Summary Background Intrahepatic non‐hypervascular hypointense nodules (NHHNs) detected during the hepatobiliary phase of gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced magnetic resonance imaging (EOB‐MRI) have the potential to transition into typical hypervascular hepatocellular carcinoma (HCC). However, the incidence and risk factors for the emergence of these nodules in patients with chronic hepatitis C virus (HCV) infection are unknown. Aim To investigate the incidence and risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…We appreciate the comments by Dr Crane et al on our study . We agree that the majority of the patients in our study were at high risk for hepatocellular carcinoma (HCC) . However, one important finding of this study was that no non‐hypervascular hypointense nodules (NHHNs) emerged in patients with low FIB‐4 index (<1.45).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…We appreciate the comments by Dr Crane et al on our study . We agree that the majority of the patients in our study were at high risk for hepatocellular carcinoma (HCC) . However, one important finding of this study was that no non‐hypervascular hypointense nodules (NHHNs) emerged in patients with low FIB‐4 index (<1.45).…”
supporting
confidence: 50%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementmentioning
confidence: 99%
“…The most recent study by Toyoda et al reports on the emergence of NHHN in 515 patients with HCV infection and without baseline NHHNs. NHHNs emerged over 5 years in 24% of patients with advanced fibrosis/cirrhosis (Fib‐4 ≥ 3.25), and in 7.2% of those with some fibrosis (Fib‐4 1.45‐3.23), but did not occur in those without fibrosis (Fib‐4 ≤ 1.45) . No other baseline factor was independently associated with the emergence of NHHNs.…”
mentioning
confidence: 98%
“…This result indicates that NHHNs may be precancerous lesions. Furthermore, the authors’ group recently showed that a high FIB‐4 index was the only independent risk factor associated with the occurrence of NHHNs in HCV patients 7 . Therefore, SVR by DAAs may be related to improved prognosis in patients with NHHNs since it reduces the incidence of hypervascularity, especially in those with advanced liver fibrosis.…”
mentioning
confidence: 99%